PERAN KJRI KOTA KINABALU DALAM MENINGKATKAN AKSES PENDIDIKAN BAGI ANAK-ANAK BURUH MIGRAN INDONESIA (BMI) DI SABAH - Herning Suryo, Laura Rema Andita, Christy Damayanti & (Transformasi, 2016)
Sabah is a state in Malaysia which has a huge number of Indonesian Migrant Workers. Thepopulation of migrant workers are pretty much the responsibility of the Consulat General ofIndonesia in Kinabalu., including the issue of education is a right that must be fought by theIndonesian state irrespective of existence that are outside the territory of Indonesia. By usingthe theory of national interest, diplomacy, and nationalism, researchers conducted a study onhow the role of the Consulate General of Indonesia in Kinabalu to improving access ofeducation for the children migrant worker in Sabah. This study used a qualitative descriptivemethod using primary and secondary data., when Andhika Bambang Supeno as the ExecutingSocial and Cultural Consulate General of Indonesia in Kinabalu and Shelya Regina as ateacher of art and culture at Indonesian School in Kinabalu. Results can be concludedConsulate General of Indonesia in Kinabalu‟s role in improving access of education forchildren of migrant workers in Sabah which is done through a function representing,negotiating, and protecting not optimal because. 1. Internal factors, namely the limited financialand human resources support. 2. External factors, consent of the State Government of Sabah. 3.The lack of awareness of parents of children of migrant workers on the importance of educationalso that educational access location of residence. In the scale of international relations, therole of the Consulate General of Indonesia in Kinabalu could improve bilateral relationsbetween Indonesia and Malaysia, particularly the education of children of migrant workers.Key words: access of education, the role of the Consulate General of Indonesia in Kinabalu